Новый род саркофагин (Diptera, Sarcophagidae) из Эфиопии - Вервес, Ю.Г. (Вестник зоологии, 1984)
A New Sarcophaginae Fly Genus (Diptera, Sarcophagidae) from Ethiopia. Verves Yu. G.— Vestn. zool., 1984, No. 2. Amharomyia gen. n. Type species by original designation and monotypy — A. macuiigaster sp. n. The new genus is similar to Poecilometopa Vill, differs by bare propleuron, presence of one dark spot on wing, and details